Dyke magnetization, magnetostratigraphy and upper-crustal structure in the Reydarfjordur area of eastern Iceland (Dataset) ... - J.D.A. Piper; M.G. Fowler; I.L. Gibson (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Dyke magnetization, magnetostratigraphy and upper-crustal structure in the Reydarfjordur area of eastern Iceland ...